Resposta :
Resposta:
Explicação passo-a-passo:
Solução:
temos:
P(-2, 3)
m = -5
Conhecendo o ponto P(-2, 3) e m = -5, basta substituir esses valores na equação fundamental da reta.
Logo:
y - yP = m.(x - xP)
y - 3 = -5.[(x - (-2)]
y- 3 = -5.[x + 2]
y - 3 = -5x - 10
y = -5x - 10 + 3
y = -5x - 7
5x + y = -7
5x + y + 7 = 0
Resposta: 5x + y + 7 = 0
Resposta:
[tex]\textsf{Leia abaixo}[/tex]
Explicação passo-a-passo:
[tex]\mathsf{y - y_0 = m(x - x_0)}[/tex]
[tex]\mathsf{y - 3 = -5(x - (2))}[/tex]
[tex]\mathsf{y - 3 = -5(x + 2)}[/tex]
[tex]\mathsf{y - 3 = -5x - 10}[/tex]
[tex]\boxed{\boxed{\mathsf{y = -5x - 7}}}\leftarrow\textsf{equa{\c c}{\~a}o reduzida}[/tex]
[tex]\boxed{\boxed{\mathsf{5x + y + 7 = 0}}}\leftarrow\textsf{equa{\c c}{\~a}o geral}[/tex]